2014
DOI: 10.1007/s10596-013-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint formulation and constraint handling for gradient-based optimization of compositional reservoir flow

Abstract: An adjoint formulation for the gradient-based optimization of oil-gas compositional reservoir simulation problems is presented. The method is implemented within an automatic differentiation-based compositional flow simulator (Stanford's AD-GPRS). The development of adjoint procedures for general compositional problems is much more challenging than for oil-water problems due to the increased complexity of the code and the underlying physics. The treatment of nonlinear constraints, an example of which is a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Therefore, the time step refinement affects the search for the optimal solution. Previous numerical studies of the SQP algorithm have shown that the optimization with constrained simulation has better performance than constrained optimization [14,25]. In this work, we use different time step refinement strategies to explain the observed difference.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, the time step refinement affects the search for the optimal solution. Previous numerical studies of the SQP algorithm have shown that the optimization with constrained simulation has better performance than constrained optimization [14,25]. In this work, we use different time step refinement strategies to explain the observed difference.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to robust optimization studies there is a large number of papers describing deterministic well control optimization over the life cycle of the reservoir both with and without the use of gradients; see, e.g., Sudaryanto and Yortsos (2000), , Sarma et al (2008b), van Essen et al (2010), Forouzanfar et al (2013a, Kourounis et al (2014) or, for overviews, Jansen (2011) andEcheverr谋a Ciaurri et al (2011). Moreover, all of the CLRM studies referred to in Section 3 involve robust or deterministic well control and/or well location optimization.…”
Section: Application Case Reservoir Engineering -Long-term Reservoir mentioning
confidence: 99%
“…Nonlinear inequality constraints are generally much more difficult to implement and various approaches have been explored. We refer to Jansen (2011), Kourounis et al (2014), Sarma et al (2008) for further discussion.…”
Section: Adjoint-based Optimizationmentioning
confidence: 99%
“…Adjoint-based approaches were first applied for well control optimization by Ramirez (1987). More recently, these techniques have been incorporated by, e.g., Brouwer and Jansen (2004), Sarma et al (2008), van Essen et al (2011, Kourounis et al (2014). For further references, see the review paper Jansen (2011).…”
Section: Introductionmentioning
confidence: 99%